2015
DOI: 10.17219/acem/32577
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9 Polymorphism and Unstable Anticoagulation with Warfarin in Patients Within the First 3 Months Following Heart Valve Replacement

Abstract: Background. Warfarin dose requirements are partly determined by common single nucleotide polymorphisms in VKORC1 and CYP2C9 genes. Objectives. The aim of this study was to investigate how the presence of allelic variants in CYP2C9 affects the stability of anticoagulation in patients within the first 3 months following elective heart valve replacement. Material and Methods. In a case-control study we compared 18 consecutive carriers of CYP2C9*2 and/or *3 and 25 well-matched patients with the wild type CYP2C9*1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although no significant association was observed between median TTR and the polymorphisms analyzed, this data may be a consequence of either sample size or chronic patients, since another study has already shown this association. 13 In a cohort study conducted in Canada with 1059 patients taking warfarin, the average time in the therapeutic interval was 56% (± 25%) in the three months after start of treatment and 70% (± 21%) in the 3 to 12 months interval. Independent predictors of inadequate anticoagulation control were chronic kidney disease, heart failure, dyslipidemia and age.…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant association was observed between median TTR and the polymorphisms analyzed, this data may be a consequence of either sample size or chronic patients, since another study has already shown this association. 13 In a cohort study conducted in Canada with 1059 patients taking warfarin, the average time in the therapeutic interval was 56% (± 25%) in the three months after start of treatment and 70% (± 21%) in the 3 to 12 months interval. Independent predictors of inadequate anticoagulation control were chronic kidney disease, heart failure, dyslipidemia and age.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, CYP3A4, as the most important metabolism enzymes, not only accounts for up to 30% of the total hepatic CYP450s proteins but also involved in almost 50% metabolism of therapeutic drugs [27]. CYP2C9 has played a key role in the process of a variety of drugs, especially in those with a narrow therapeutic range, such as phenytoin sodium and warfarin [28-30]. Meanwhile, these 2 enzymes have been proved to play an important part in the biotransformation of anticancer agents in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature is very controversial (Apostolakis et al, 2013Pokorney et al, 2015. Among the genetic factors, polymorphisms in the CYP2C9 and VKORC1 genes have already been associated with TTR (Park et al, 2015(Park et al, , 2017Wypasek et al, 2015;Bryk et al, 2018). More recently, a GWAS reported that two SNPs (rs17791091 and rs4379440) in ASPH gene are associated with TTR (Eriksson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%